1995
DOI: 10.1029/95jc01961
|View full text |Cite
|
Sign up to set email alerts
|

Mean sea level and surface circulation variability of the Mediterranean Sea from 2 years of TOPEX/POSEIDON altimetry

Abstract: We describe the circulation and mean sea level variations of the Mediterranean Sea from 2 years of TOPEX/POSEIDON altimetric data. It is first shown that the response of the Mediterranean Sea to atmospheric pressure forcing is close to an inverse barometer (except at high frequencies) which means that the adjustment is accompanied by a flow through the Straits of Sicily and Gibraltar. We then use TOPEX/POSEIDON to study the mean sea level variations, representing steric effects and integrated large‐scale chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
77
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(80 citation statements)
references
References 29 publications
3
77
0
Order By: Relevance
“…SLA maps of the Mediterranean Sea are regularly produced by Collecte Localisation Satellites (CLS) in Toulouse, France, from the combination of data of the ERS and TOPEX/Poseidon altimeters, by subtracting a four-year mean value from the actual measurements. Besides the usual corrections, data are low-pass filtered to reduce altimetric noise and SLA maps are built on a regular grid of 0.2 x 0.2 degrees every 10 days using an improved space/time objective analysis method (Larnicol et al, 1995;LeTraon et al, 1998).…”
Section: Radar Altimeter Measurementsmentioning
confidence: 99%
“…SLA maps of the Mediterranean Sea are regularly produced by Collecte Localisation Satellites (CLS) in Toulouse, France, from the combination of data of the ERS and TOPEX/Poseidon altimeters, by subtracting a four-year mean value from the actual measurements. Besides the usual corrections, data are low-pass filtered to reduce altimetric noise and SLA maps are built on a regular grid of 0.2 x 0.2 degrees every 10 days using an improved space/time objective analysis method (Larnicol et al, 1995;LeTraon et al, 1998).…”
Section: Radar Altimeter Measurementsmentioning
confidence: 99%
“…Pioneering studies (Larnicol et al, 1995;Iudicone et al, 1998;Ayoub et al, 1998) have demonstrated the usefulness of satellite altimetry for monitoring oceanographic conditions in marginal seas like the Mediterranean Sea. However, it is clear that corroborative information and any available in situ data from historical archives are often indispensable to validate satellite-derived results and to give them the correct interpretation on the basis of the regional phenomena.…”
Section: Introductionmentioning
confidence: 99%
“…This seasonal cycle of the zooplankton activity along the Moroccan coast is related to the upwelling cycle which develops in spring, is reinforced in summer, attenuates in autumn and decreases in winter (Furnestin, 1959;Thiriot, 1978;Belvèze, 1991;Orbi & Nemmaoui, 1992 ). Thus, the zooplankton activity in M'Diq can be related to the seasonal cycle of the Mediterranean water mass which follows change of flow entering and outgoing through the Gibraltar Strait (Larnicol et al, 1995;Traon et al, 2007). Moreover, Fernandez de Puelles et al, (2003) showed a seasonal cycle related to an oscillation of the zooplankton abundance with maximum values recorded during the first six months of the year.…”
Section: Discussionmentioning
confidence: 99%